Some Issues About the Norwegian Capital Income Imputation Model - Karl Ove Aarbu (Statistics Norway, Research Department, 1995)
This paper will focus on a particular provision in the Norwegian tax reform of 1992, the imputation of capital income for self employed and small incorporated firms with active owners. A simple user cost model is derived, and this model is used to discuss the impact on investment incentives that stems from imputation of capital income. Within this framework, we discuss potential distortions that stem from certain elements in the Norwegian tax code. The formalised approach allows us to focus more on the assumptions underlying the analysis, and we show that the user cost of capital is dependent of the discount rate. We also use our approach to calculate potential tax wedges. The calculations show that the distortions can be quite large, under realistic assumptions.
Keywords: H21; H25; 330; Cost of capital; self employed; taxes; tax reform.